Pelatihan Kompetensi dan Bimbingan Digital Marketing untuk Peningkatan Kapasitas Kewirausahaan Anggota PKK Desa Gunasari Kabupaten Sumedang - Sari Sri Handani; Dena Mustika; Rini Ayu Susanti; Hendra Prijatna (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
The writing of this community service journal is the result of activities carried out to be able to provide socialization of the importance of having competence and understanding digital marketing for increasing entrepreneurial capacity and also the challenges of the industrial revolution 4.0 era. This community service activity was carried out in Gunasari Village, South Sumedang District, Sumedang Regency. This training and guidance was given to PKK members in Gunasari Village. This activity is carried out as an effort to improve digital marketing competencies and capabilities in the hope of increasing entrepreneurial capacity. So that this achievement is expected to form independence and strengthen the family and community economy